2021
DOI: 10.3390/biomimetics6040071
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired and Post-Functionalized 3D-Printed Surfaces with Parahydrophobic Properties

Abstract: Desertification is a growing risk for humanity. Studies show that water access will be the leading cause of massive migration in the future. For this reason, significant research efforts are devoted to identifying new sources of water. Among this work, one of the more interesting strategies takes advantage of atmospheric non-liquid water using water harvesting. Various strategies exist to harvest water, but many suffer from low yield. In this work, we take inspiration from a Mexican plant (Echeveria pulvinate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Additionally, the aggressive conditions used to convert Cu to Cu(OH) 2 may degrade PLA (saponification), particularly at the edge of the blades or meshes. The partial saponification of PLA during oxidation has already been reported in the literature and can be confirmed by simple IR observation ( Figure S1 ) [ 44 ]. For the same surface design, the differences in roughness depending on the functionalization may be significant, but it remains in the same range for most of the cases (all numerical data presented as supplementary data).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Additionally, the aggressive conditions used to convert Cu to Cu(OH) 2 may degrade PLA (saponification), particularly at the edge of the blades or meshes. The partial saponification of PLA during oxidation has already been reported in the literature and can be confirmed by simple IR observation ( Figure S1 ) [ 44 ]. For the same surface design, the differences in roughness depending on the functionalization may be significant, but it remains in the same range for most of the cases (all numerical data presented as supplementary data).…”
Section: Resultssupporting
confidence: 83%
“…These observations on functionalized confirmed the roughness measurements and showed that the functionalized surfaces present thin nano-crystallization as described for such kind of functionalization in the literature [ 44 , 45 , 46 ]. Most of the prepared surfaces exhibit strong hydrophobicity, with contact angles greater than what has been reported for a simple plate functionalized with a similar procedure [ 44 ]. This is particularly evident for GVB and PVB modified with long linear carboxylic acids (C6 to C18).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is particularly true in desert or semidesert regions where water is scarce and plants and animals need to optimize water-capture and -retention strategies. One can take inspiration from plants or animals to prepare surfaces suitable for water harvesting applications [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%